Review immune response of targeting CD39 in cancer - Yao Liu; Zhongliang Li; Xiaoguang Zhao; Jing Xiao; Jiacheng Bi; Xian-Yang Li; Guokai Chen; Ligong Lu (BMC, 2023)
Abstract The ATP-adenosine pathway has emerged as a promising target for cancer therapy, but challenges remain in achieving effective tumor control. Early research focused on blocking the adenosine generating enzyme CD73 and the adenosine receptors A2AR or A2BR in cancer. However, recent studies have shown that targeting CD39, the rate-limiting ecto-enzyme of the ATP-adenosine pathway, can provide more profound anti-tumor efficacy by reducing immune-suppressive adenosine accumulation and increasing pro-inflammatory ATP levels. In addition, combining CD39 blocking antibody with PD-1 immune checkpoint therapy may have synergistic anti-tumor effects and improve patient survival. This review will discuss the immune components that respond to CD39 targeting in the tumor microenvironment. Targeting CD39 in cancer has been shown to not only decrease adenosine levels in the tumor microenvironment (TME), but also increase ATP levels. Additionally, targeting CD39 can limit the function of Treg cells, which are known to express high levels of CD39. With phase I clinical trials of CD39 targeting currently underway, further understanding and rational design of this approach for cancer therapy are expected.